Avoiding a ‘Catch 22’—Major Lessons From a Meta-Analysis of Reports of the Parliament of Western Australia on Threats to Sovereignty by National Uniform Legislation - Guzyal Hill (Bond Law Review, 2021)
National uniform legislation has served as an instrument to attune federalism to new realities. The enactment of national uniform legislation is not a panacea. However, it is critical that when harmonisation is necessary, it is efficient and effective, results in long-lasting uniformity and does not encroach on the sovereignty of the State and Territory Parliaments. The problem is that national uniform legislation is often called to address complex legal issues, respond to a multifaceted debate and meet the demands of actors from divergent ideological backgrounds. This testing backdrop results in politically charged arguments that often is presented as a false dilemma between sovereignty and national uniform legislation, ‘catch 22’. To date, there has been lack of systematic objective analysis on what would be an example of this encroachment on sovereignty before the allegation of encroachment arise in the State or Territory Parliaments. This article seeks to address this gap through empirical methods. To ensure objectivity, a meta-analysis of 173 reports was undertaken. Contrary to political statements, the empirical findings suggest the cases of encroachment were rare and were isolated to specific practices. Legislative drafters, policymakers and law reformers must refrain from these practices if they wish to avoid the ‘catch 22’ of choosing between uniformity and sovereignty.